2007
DOI: 10.21273/jashs.132.6.790
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Watermelon and Related Species for Resistance to Race 1W Powdery Mildew

Abstract: Powdery mildew [Podosphaera xanthii (Castagne) Braun & Shishkoff (syn. Sphaerotheca fuliginea auct. p.p.)] is now a common disease on watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai] in the United States. In this study, the entire available U.S. Plant Introduction collection of Citrullus Schrad. ex Eckl. & Zeyh. species was evaluated for resistance to P. xanthii Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 11 publications
11
53
0
Order By: Relevance
“…This species is generally considered to be highly resistant to CPM (Sitterly 1978). Our recent data represent the first report of a GC infection on watermelon in the Czech Republic, and it complements the recent findings of Davis et al (2007).…”
Section: Discussionsupporting
confidence: 88%
“…This species is generally considered to be highly resistant to CPM (Sitterly 1978). Our recent data represent the first report of a GC infection on watermelon in the Czech Republic, and it complements the recent findings of Davis et al (2007).…”
Section: Discussionsupporting
confidence: 88%
“…The reactions of these differentials have been considered to be consistent worldwide (McCreight, 2006). The melon race 1 in our study could also be designated as race 1M based on suggestions by Davis et al (2007). Recently Davis et al (2007) described race 1W from watermelon and suggested that this race did not infect melons.…”
Section: Resultssupporting
confidence: 54%
“…Two days before inoculation, air was blown over leaves of 'Iran H' or squash plants to clear the old conidia and allow new conidia to form. Three weeks after seeding, seedlings were dusted with powdery mildew conidia as described by Thomas et al (2005) and others (Davis et al, 2006b(Davis et al, , 2007. Seedlings were maintained in the greenhouse where conditions were optimal for development of powdery mildew during the winter months.…”
Section: Methodsmentioning
confidence: 99%
“…The US PIs of P. fistulosus were included in several studies that evaluated Citrullus germplasm for disease or pest resistance (Simmons and Levi 2002;Davis et al 2007;Hopkins and Levi 2008) with the idea that the resistant P. fistulosus PIs could be used in breeding programs aimed at enhancing resistance in watermelon cultivars. The results herein confirmed that P. fistulosus is closer to B. hispida and is distant from Citrullus or Cucumis species.…”
Section: Resultsmentioning
confidence: 99%